Indian Model of Integrated Healthcare (IMIH): a conceptual framework for a coordinated referral system in resource-constrained settings - Moonis Mirza; Madhur Verma; Arun Aggarwal; Sidhartha Satpathy; Soumya Swaroop Sahoo; Rakesh Kakkar (BMC Health Services Research, 2024)
Abstract Introduction With the escalating burden of chronic disease and multimorbidity in India, owing to its ageing population and overwhelming health needs, the Indian Health care delivery System (HDS) is under constant pressure due to rising public expectations and ambitious new health goals. The three tired HDS should work in coherence to ensure continuity of care, which needs a coordinated referral system. This calls for optimising health care through Integrated care (IC). The existing IC models have been primarily developed and adopted in High-Income Countries. The present study attempts to review the applicability of existing IC models and frame a customised model for resource-constrained settings. Methods A two-stage methodology was used. Firstly, a narrative literature review was done to identify gaps in existing IC models, as per the World Health Organization framework approach. The literature search was done from electronic journal article databases, and relevant literature that reported conceptual and theoretical concepts of IC. Secondly, we conceptualised an IC concept according to India's existing HDS, validated by multiple rounds of brainstorming among co-authors. Further senior co-authors independently reviewed the conceptualised IC model as per national relevance. Results Existing IC models were categorised as individual, group and disease-specific, and population-based models. The limitations of having prolonged delivery time, focusing only on chronic diseases and being economically expensive to implement, along with requirement of completely restructuring and reorganising the existing HDS makes the adoption of existing IC models not feasible for India. The Indian Model of Integrated Healthcare (IMIH) model proposes three levels of integration: Macro, Meso, and Micro levels, using the existing HDS. The core components include a Central Gateway Control Room, using existing digital platforms at macro levels, a bucket overflow model at the meso level, a Triple-layered Concentric Circle outpatient department (OPD) design, and a three-door OPD concept at the micro level. Conclusion IMIH offers features that consider resource constraints and local context of LMICs while being economically viable. It envisages a step toward UHC by optimising existing resources and ensuring a continuum of care. However, health being a state subject, various socio-political and legal/administrative issues warrant further discussion before implementation.